Management of Vocal Fold Paralysis and Dysphagia for Neurologic Malignancies in Children. (November 2019) - Nagy, Peter; Beckmann, Nicholas; Cox, Steven; Sheyn, Anthony
Objectives: To evaluate our experience with a significant number of brain malignancy–related vocal fold paralysis patients and their response to vocal cord–related therapies. Background: Vocal fold paralysis is a potentially devastating complication of various types of pediatric diseases and surgeries that can lead to significant vocal and swallowing difficulties. While there is significant data in the literature on outcomes of children treated for vocal fold paralysis following cardiac or thyroid surgery, there is a scarcity of such information on children following the treatment of neurologic malignancy. Methods: Records of 19 patients at a tertiary center who were treated for neurologic malignancies and developed either unilateral or bilateral vocal fold paralysis were reviewed for vocal fold pathology and vocal fold paralysis treatment-related variables, including initial diagnosis, management with observation or speech therapy, duration of therapy, pre- and postintervention swallow studies, and surgical intervention. Results: Bilateral vocal fold paralysis was noted in 26% (5/19) patients. Eighty-four percent (16/19) of patients had stable or improved ability to vocalize and swallow following therapy. There was no statistically significant difference in speech or swallowing improvement after speech therapy alone or speech therapy in combination with injection laryngoplasty ( P = .25). No complications were noted with surgical intervention. Conclusions: Patients with vocal fold paralysis secondary to neurologic malignancy can have an improvement in speech and swallowing after a variety of treatments, including speech therapy or early injection laryngoplasty. There was no statistically significant difference in improvement based on the type of intervention utilized. A larger sample size is needed to conclude whether surgical intervention combined with speech therapy leads to more rapid and significant functional improvement than speech therapy alone.